Tanggung Jawab Hukum Perusahaan Skincare Terhadap Klaim Iklan yang Menyesatkan: Analisis Berdasarkan Peraturan Perlindungan Konsumen di Indonesia - Linsepda Limbong (CV Rewang Rencang, 2025)
The Indonesian skincare industry is rapidly growing with technological innovations and high digital penetration. However, overclaims in product advertising remain a major challenge threatening consumers. BPOM regulations and Consumer Protection Law ensure consumer protection through strict supervision and transparent claims based on scientific evidence. Enforcement of administrative to criminal sanctions is key to maintaining industry integrity. Collaboration among regulators, businesses, and consumers is crucial for creating a healthy and sustainable skincare market ecosystem.